Oxygen mobility in Bi : Sr : Ca : Cu : O ceramic measured using anelastic relaxation methods - Gimenez, JMA; de Almeida, L. H.; Grandini, Carlos Roberto [UNESP]; de Souza, F. L.; Santos, Dayse Iara dos [UNESP]; Salgado, L.; Filho, F. A. (Trans Tech Publications Ltd, 2003)
Since the discovery of YBaCuO, experiments have shown that its superconducting properties are strongly affected by the oxygen content. More recently, anelastic relaxation measurements in La2CuO4+delta, showed that the decrease in the oxygen content can be related to two events. One is the decrease in mobility between two adjacent CuO planes, and the other is the increase in the number of tilting patterns of the CuO6 octahedra. In the case of the bismuth-based ceramic, it is known that the oxygen content, within some limits, does not affect its superconducting properties. In order to evaluate the mobility and the effect of the oxygen content on this material we have prepared BSCCO ceramic and tested regarding its internal friction and electrical resistivity as a function of the temperature while the oxygen content was being reduced by a sequence of vacuum annelaing at 620 K. The samples were prepared in the Bi:Sr:Ca:Cu = 2212 and 2223 proportion, using powder obtained by the sol-gel route and conventional solid state reaction. The anelastic relaxation measurements were performed using a torsion pendulum operating with frequency about 15-35 Hz between 77 to 700 K. The diffraction pattern of the as sintered and the vacuum annealed material were also presented. The results have shown complex anelastic relaxation structures that were associated to the jump of interstitial oxygen atoms between two adjacent CuO planes. The vacuum annealing showed to be deleterious to the critical temperature of the superconducting ceramic.
Keywords: oxygen mobility; internal friction; superconducting oxides